Derivations of a Sullivan Model and the Rationalized G-Sequence. (1st February 2021) - Maphane, Oteng
Abstract : Let G k, n ℂ for 2 ≤ k < n denote the Grassmann manifold of k -dimensional vector subspaces of ℂ n . In this paper, we compute, in terms of the Sullivan models, the rational evaluation subgroups and, more generally, the G -sequence of the inclusion G 2, n ℂ ↣ G 2, n + r ℂ for r ≥ 1 .